Theoretical researches of process of transport-expeditionary maintenance of owners of goods by a railway transport in the conditions of market relations - Кіхтєва, Юлія Володимирівна; Челмакіна, Олена Сергіївна (Eastern-European Journal of Enterprise Technologies, 2012)
The review of theoretical researches of questions of transport-expeditionary maintenance of goods owners is conducted by a railway transport .The direction of prospective research in the organization of the robot unit of railway transport is stated